Sie sind auf Seite 1von 7

1

Assignment 8 — Solutions 3/10/04

Problem 5.22

Choose coordinates so that the infinite plane is the x-y plane (z = 0) and the bar is at some infinitesimal distance h

÷÷÷” ÷÷” ÷÷÷”

above the plane. From the discussion in §5.9C a hard ferromagnet is equivalent to a system with an effective
magnetic current density. For M = M z` there is only the effective surface current K = M ä n` where n` is the unit
normal to the vertical surface (in general a function of position, though most of you took the bar to be a cylinder.
The important thing for now is that n` is perpendicular to z` ). Applying the results of 5.17 we see that the system is
equivalent to an image current distribution with components scaled by Hmr - 1L ê Hmr + 1L (amongst other things).
Since mr ª m ê m0 = ¶ for our case, this factor reduces to H1 - 1 ê mr L ê H1 + 1 ê mr L Ø 1. We see that all we need is
the "reflected" current (recall that there is no z component since z` ä n` must lie in the x-y plane, and actually no z-
dependence at all since the bar is uniform in the z-direction) and corresponding image magnetization:

÷÷”*
K Hx, y, zL = Kx Hx, y, -zL x`
z A z

+K y Hx, y, -zL y`
µ0

÷÷÷”* ÷÷÷”
JJK
M = M zˆ

M = M h h -------
ϖ ϖ
Image bar located with "top" end-cap -h -h ++++++++

at z = -h. JJK *
M
µ =∞

The field due to the image can be calculated from its magnetic scalar potential 5.99, but this is hard for a bar of

÷÷÷” ÷÷÷”
M = M z` = constant there is only the effective surface charge sM = H≤ z` L ÿ M = ≤M where the upper sign is for
arbitrary cross-section. Instead we look at things from the effective magnetic charge density point of view. For

÷÷÷”*
* = H≤ z` L ÿ M
the upper end-cap and the lower for the lower end-cap. Since the bar is very long we will neglect the effect of the
upper end-cap. Similarly there are effective surface charges sM = ≤M for the image bar, and we will
ignore the lower end-cap of this. In summary we have two surfaces with equal and opposite constant charge
density as shown in the second diagram.
÷÷÷”
÷ ” ÷÷÷”
analogous to the electrostatic problem (with E Ø H and 1 ê e0 Ø m0 ) of a charge distribution above an infinite
Because the material is infinitely permeable, the H -field must be perpendicular to the z = 0 boundary. Now this is

conducting plane and a corresponding image charge distribution below. As discussed in problem 2.9 of homework

÷” ÷” ÷” ÷ ”*
set 3 the force on a small patch of the image charge (which has normal z` ) is
F = ÅÅÅÅ1Å IE > + E < M s a = Hs2 ê 2 e0 L z` a for a conductor, and so by analogy F = Hm0 sM
* 2 ê 2L z` a for the
2
magnetic case. The force on the magnetic charge must be equal and opposite, so

÷” ÷ ”*
F = - ® F = - ® a ÅÅÅÅÅÅÅÅÅ s*M 2 z` = - ÅÅÅÅÅÅÅÅÅ M 2 z` ® a = - ÅÅÅÅÅÅÅÅÅ M 2 A z`
m0 m0 m0
S S 2 2 S 2
2

Problem 5.30

(a) Let S denote the cylinder surface, then

÷” ” £
J Hx L = KHfL dHv - RL z` , KHfL = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
I cos f

÷” ” £
÷” ” J Hx L
2R

AHxL = ÅÅÅÅÅÅÅÅ0ÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

” ” ‡ ” ÅÅÅÅÅÅÅÅÅ”ÅÅÅ£ÅÅÅÅÅ , x” £ = R cos f£ x` + R sin f£ y` + z£ z`
m m0 ` I cos f£
†x - x § 2 R †x - x §
ÅÅÅÅÅ = ÅÅÅÅ
Å ÅÅÅ
Å Å z 2 x£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4p £ 4p S

Expand using 3.149 where v< (v> ) is the smaller (larger) of v and R:

i1 y
£ LD jjj ÅÅÅÅÅ Hk L Hk L Hf £ LD I Hk v L K Hk v Lzzz
‡ j
j2 0 ‚ zz
†x” - x” £ §
¶ ¶
1 4
k {
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅ = ÅÅÅÅ
Å k cos@kHz - z I v< K0 v> + cos@m - f m < m >
p 0

÷”
m=1

The A integral picks out the m = 1 term by orthogonality of cosines in the range 0 § f£ § 2 p. Using
cos Hf - f£ L = cos f cos f£ + sin f sin f£ and the orthogonality of sines and cosines, the f£ integral is
Ÿ0 f£ cos f£ cosHf - f£ L = cos f Ÿ0 f£ cos2 f£ = p cos f:
2p 2p

÷” ”
AHxL = ÅÅÅÅÅÅÅÅÅÅ z` ‡ R f£ ‡ z£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ‡ k cos@kHz - z£ LD cosHf - f£ L I1 Hk v< L K1 Hk v> L
m0 2p ¶ I cos f£ 4 ¶

4p 0 -¶ 2R p 0
= ÅÅÅÅÅÅÅÅÅÅÅÅÅ z cos f ‡ z£ ‡ k cos@kHz - z£ LD I1 Hk v< L K1 Hk v> L
m0 I ` ¶ ¶

2p -¶ 0

2 p dHkL = Ÿ-¶
¶ £
z£ ‰-Â k z
Ÿ-¶ z cos@kHz - z LD = ReI‰
Â k z ¶ z£ ‰-Â k z M = Re@‰Â k z 2 p dHkLD:
d-function
Ÿ-¶
From the representation we have
¶ £ £ £

÷” ”
AHxL = m0 I z` cos f ‡ k ReA‰Â k z dHkL I1 Hk v< L K1 Hk v> LE

Applying the asymptotic form 3.102 (since the arguments of I1 and K1 approach 0 due to the d-function):
ÄÅ É
÷” ” ÅÅ Â k z 1 i k v< y GH1L ij 2 yzÑÑÑ
AHxL = m0 I z cos f ‡ k ReÅÅ‰ Å j z
dHkL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ z ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑ
j z
ÅÅÇ GH2L k 2 { 2 k k v> {ÑÑÖ

`

Ä
Å É ÄÅ É
` cos f ¶ k ReÅÅÅdHkL ÅÅÅÅÅÅÅÅ v< ÑÑÑ ` cos f ReÅÅÅ ¶ k dHkL ÅÅÅÅÅÅÅÅ v< ÑÑÑ
Ñ ÑÑ
0

‡ ÅÅ Ñ ÅÅ‡
ÅÅÇ v> ÑÑÑÖ ÅÅÇ -¶ v> ÑÑÑÖ
1 1
= ÅÅÅÅÅ m0 I z Å ÅÅÅ = ÅÅÅÅÅ m 0 I z Å ÅÅÅ
2 0 4
1 v<
= ÅÅÅÅÅ m0 I cos f ÅÅÅÅÅÅÅÅÅÅÅÅ z`
4 v>

v< ê v> = v ê R for v § R and v< ê v> = R ê v for v ¥ R. The nonzero terms in the curl are:
It was necessary to double the range of so that we can properly integrate the d-function. Recall that
3

ij l
o |
o yz
jj o
o o
o z
÷” ÷” ÷” jj ` 1 o
o R ozzzz
o
1
j
B = “ ä A = v ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅ - f ÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅ m0 I jj-v ÅÅÅÅÅÅÅÅ sin f ÅÅÅÅÅÅÅÅÅÅÅÅ - f cos f m } zz
ÅÅÅÅÅÅ , v§R
jj o
o o
o zz
1 ∑ Az ` ∑ Az v< `
o o
` 1
jj o
o - ÅÅÅÅÅÅÅÅÅÅ , v ¥ R ozz
o
k n v2 ~{
v ∑f ∑v 4 v v> R

l
o
o
o
o
o
sin f ` cos f
` ÅÅÅÅÅÅÅÅ 1
ÅÅÅÅÅÅÅÅ + f ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅ y` , v § R
= - ÅÅÅÅÅ m0 I m
v
o
o
o
1
o
R R R
o ÅÅÅÅÅÅÅÅÅÅ Iv̀ sin f - f cos fM
n v2
4 R `
, v¥R

` + cos f f` we see by crossing v

From y` = sin f v ` into it that the vector potential outside the cylinder is:

m0 H-I R y` Läv ÷÷÷”

÷” 1 R 1 R ` `
A> = ÅÅÅÅÅ m0 I ÅÅÅÅÅÅÅÅ cos f z` = ÅÅÅÅÅ m0 I ÅÅÅÅÅÅÅÅ v ä y = ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4 v 4 v 4p v2
÷÷÷” ê v2 , we see that this is indeed a 2D dipole with dipole
÷÷” äv
Comparing this to the 2D version of 5.55, Hm0 ê 4 pL m
moment -I R y` .

(b) Since we're in free space, 5.148 gives for a cylinder of length :

÷”2 ÷”2
W = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x B + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡
1 1
3 x B
2 m0 v§R 2 m0 v¥R

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x J- ÅÅÅÅÅÅÅÅÅÅÅÅÅ N + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x J- ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ N Isin2 f + cos2 fM

1 m0 I 2 1 m0 I R 2
2 m0 v§R 4R 2 m0 v¥R 4 v2

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ v f ‡ z ‡ v ÅÅÅÅÅÅÅÅÅÅ

m0 I 2 m0 I 2 R2 2p  ¶ 1

Ä
ÅÅ 1 ÑÑ¶ É
32 R2 v§R 32 v4

ÅÅÅÅÅÅÅÅÅÅ p R2  + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 p  ÅÅÅÅ- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ

0 0 R

ÅÇ 2 v2 ÑÖR
m0 I 2 m0 I 2 R2 m0 p  I 2 m0 p  I 2
= ÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
32 R2 32 32 32

We see that this is equally distributed between inside and outside the cylinder, and that th energy per unit length is

W m0 p I 2
ÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
 16

(c) Since we have only one circuit W = L I 2 ê 2. Comparing to the above we read off L ê  = p m0 ê 8.

Problem 5.33
÷”
(a) Following the arrows on the diagram we see that x” 12 = -x” 2 + R + x” 1 , so
4

” ”
÷” l 1 ÿ l 2 x” 12
F 12 = - ÅÅÅÅÅÅÅÅÅÅ I1 I2 ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
†x” 12 §3
m0
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
” ” ÷”
l 1 ÿ l 2 Ix” 1 - x” 2 + RM
4p
K dlK1
= - ÅÅÅÅÅÅÅÅÅÅ I1 I2 ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷”ÅÅÅÅÅÅÅÅ
°x” 1 - x” 2 + R•
m0 K
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ x1
” ”
4p 3 I1 x12
ij ÷ ” l 1 ÿ l 2 yzz
K
j
= - ÅÅÅÅÅÅÅÅÅÅ I1 I2 ® ® jjj-“R ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ”ÅÅ zzz
÷ÅÅÅÅ
°x” 1 - x” 2 + R• {
m0 dl 2
k
JK K
” ”
4p

÷ ” ijj m0 l 1 ÿ l 2 yzz
R x2
j ÅÅÅÅÅÅ z
= I1 I2 “R jj ÅÅÅÅÅÅÅÅÅÅ ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
” - x” + ÷R”• zz
I2
k °x {
÷” ÷”
4 p
= I1 I2 “R M12 HRL
1 2

÷”
We've pulled the “R out because it's not a function of the integration variables.

(b)

” ” ” ”
÷”
“2R M12 HRL = ÅÅÅÅÅÅÅÅÅÅ “R ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
”ÅÅ = ÅÅÅÅÅÅÅÅÅÅ ® ® “R ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷ÅÅÅÅ ÷ÅÅÅÅ
”ÅÅ
°x”1 - x” 2 + R• °x” 1 - x” 2 + R•
m0 2 l 1 ÿ l 2 m0 2 l 1 ÿ l 2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4p 4p

÷”
Change integration variables x” 1 Ø x” ª x” 1 - x” 2 , and rename R ª -x” £ to put this into a form we recognize:

÷” ” ” ” ”
“2R M12 HRL = ÅÅÅÅÅÅÅÅÅÅ ® ® l 1 ÿ l 2 “2R ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
÷ ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅ ® ® l 1 ÿ l 2 “£2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
” ”
°x” + R• x” £¨¨¨§ Æ
m0 m0
†x -
1 1
ÅÅÅÅÅ = 0
4p 4p ´¨¨¨¨¨¨¨¨¨¨¨¨¨≠¨¨¨¨¨¨¨¨
0

3 ” ”£ ” ”£
÷” Å÷ÅÅÅ”Å£ÅÅÅÅ = -4 p d Hx - x L, but a little thought shows that x ∫ x over the range of integration.
Actually “£2 ÅÅÅÅÅÅÅÅ
† x-x §
1

Problem 6.11

(a) Consider the total electromagnetic momentum contained in an infinitesimal volume swept out by the
infinitesimal area DA in time Dt by the wave (which has speed c):

÷”
DP = momentum densityäareaälength = ÷g” DA c Dt

÷ ” DP ÷”
ÅÅÅÅÅ = ÷g” DA c. The
pressure P is perpendicular force per unit area. For normally incident radiation ÷g” is already perpendicular, so
From conservation of momentum, the force is due to the transfer of this momentum, F = ÅÅÅÅ
Dt

S energy time
P = g c = ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ä ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = energy per unit volume
c areaä time length

(b) We are given S º 1.4 kW ê m2 . From Newton's law the acceleration due to the radiation pressure is
5

1.4 kW ê m2
ÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅ ÅÅÅÅÅÅ º ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º 4.67ä 10-3 m ë s2
3.0ä108 m ê s 1 g ê m2
force pressureä area S A 1
mass mass c m

(rounding up) 10 protons ê cm3 and has average speed 500 km ê s. If all of the kinetic energy is transferred to the
According to http://pluto.space.swri.edu/IMAGE/glossary/solar_wind.html the solar wind particle density averages

awind = ÅÅÅÅÅ Hwind densityLäHwind speedL2 ÅÅÅÅÅÅ º ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ä I500ä103 m ê sM ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1 10ä1.67ä10-22 kg
H10-2 mL 1 g ê m2
1 A 2 1
2 m 2 3

º 2.09ä10-6 m ë s2 ` arad H! L

Problem 6.20

rHx” , tL = dHxL dHyL d£ HzL dHtL

÷”
Jz Hx” , tL = -dHxL dHyL dHzL d£ HtL , J Hx” , tL = Jz Hx” , tL z`
” rHx”£ , tL 3 x£ dHx£ L dHy£ L d£ Hz£ L dHtL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
‡ ” ” ‡
†x - x£ § †x - x” £ §

1 3 £ 1 1
FHx, tL = ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å ÅÅÅ
Å Å  x ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å ÅÅÅ
Å Å  ÅÅÅÅÅ
4 p e0 4 p e0

Recall that Ÿ z d£ HzL f HzL = - f £ H0L which follows from integration by parts, and using the usual formula
∑†b x” - c”§n ê ∑†x” § = n †b x” - c”§n-2 Hb †x” § - c” ÿ x` L together with r ª †x” §:

” `
i ∑ yz ij -z£ - x ÿ z yz
FHx” , tL = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL jj ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
” z j
” ÅÅÅÅÅÅ z
k ∑ z£ †x - z£ z§ {z£ =0 k †x - z£ z§3 {z£ =0
1 1 1 1 z
ÅÅÅÅÅ`ÅÅÅ
ÅÅ = - ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å ÅÅÅ
Å Å dHtL - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
` = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL ÅÅÅÅÅÅÅÅ
4 p e0 4 p e0 4 p e0 r3

(b) The transverse current is given by 6.25 and 6.29:

÷” ÷” ÷” ÷” 1 ÷ ” ∑F 1 ê c2 ÷ ”
J t = J - J l = J - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅ = -dHxL dHyL dHzL d£ HtL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ Jd£ HtL ÅÅÅÅÅÅÅÅ N
z
m0 c2 ∑t 4 p m0 e0 r3

Following the derivation of 4.20 we see that we can't just take the naïve gradient of z ê r3 without adding a d
-function term. In fact if we take ÷p” ª z` in 4.20 we get (remember that 4.20 is the negative gradient of the dipole
term in 4.10, with the correct addition):

÷” z ` ÷” ` ÷”
i 3 r H p ÿ rL - p y 3 r` Hz̀ ÿ r` L - z`
“ ÅÅÅÅÅÅÅÅ = - jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅ ÷p” dHx” Lzz = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅ z` dHx” L
4p 4p
k {
÷” i 3 r Hz̀ ÿ rL - z y
3

J t = -dHx”L d£ HtL z` + ÅÅÅÅÅÅÅÅÅÅ d£ HtL jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅ z` dHx” Lzz

r r 3 3 r 3 3
` ` ` 4p
k {
1

i y
4p
= -d£ HtL jj ÅÅÅÅÅ dHx” L z` - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ r` Hz̀ ÿ r` Lzz
r 3 3
`

k {
2 z 3
3 4 p r 3 4 p r3
6

÷” ÷”
÷” ÷” ÷” ÷”
specified by A ), so we need only worry about F and by extension E = -“ F - ∑ A ë ∑t . Using 6.48 and the hint:
(c) As mentioned in the last paragraph of §6.3 A is manifestly causal (thus so is B since that is completely

÷” 1 ÷”
A = ÅÅÅÅÅÅÅÅ0ÅÅ ‡ 3 x£ ÅÅÅÅÅÅ AJ Hx” £ , t£ LE , @ Dret ª @ Dt£ =t-Rêc , R ª †x” - x” £ §
m

÷” ” i 1 ÷” ∑ 1 y
J t Hx, tL = -d£ HtL jjdHx” L z` + ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ zz
4p R ret

k 4 p ∑z r {
÷”
1 ∑ ÄÅÅ R i 1 ÷ ”£ ∑ 1 yÉÑÑ
ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅd£ Jt - ÅÅÅÅÅÅ N jjdHx” £ L z` + ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ zzÑÑÑÑ
R ∑t ÇÅ ∑ z£ r£ {ÑÖ
∑A m0
∑t 4p c k 4p

Use the d Hx” £ L to integrate the first term and 2 p dHt - R ê cL = Ÿ-¶

k ‰Â k Ht-RêcL to rewrite the second:

÷”
1 ÷ ”£ ∑ 1
ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Jt - ÅÅÅÅÅÅ N - ÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅ ‰Â k Ht-RêcL ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
∑A m0 1 R m0 k 1 ∑2
∑t 4p r c 4p 2 p R ∑t2 4p ∑ z£ r£

‰Â k Ht-RêcL
“£2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅ “£2 ‰Â k Ht-RêcL + ‰Â k Ht-RêcL “£2 ÅÅÅÅÅÅ
1 1

= ÅÅÅÅÅÅ H-Â k ê cL2 ‰Â k Ht-RêcL - ‰Â k Ht-RêcL 4 p dHx” - x”£ L

R R R
1

1 ∑2 ‰Â k Ht-RêcL
= ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ‰Â k t 4 p dHx” - x” £ L
R

c2 ∑t2
÷”
R

ij £2 ‰Â k Ht-RêcL y ÷ ”£ ∑ 1
ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ jj“ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‰Â k t dHx” - x” £ Lzzz “
j z ÅÅÅÅÅÅÅÅÅ£ÅÅÅ ÅÅÅÅ£ÅÅ
∑A m0 1 m0 c2 k
∑t 4p r 4p 2p k 4pR { ∑z r

Using d Hx” - x” £ L to integrate the last term, the remaining integral over ‰Â k t produces a d-function. We also use

term over to the 1 ê r£ , producing another d-function [remember the normalization “£2 H1 ê r£ L = -4 p d3 Hx” £ L]:
Green's theorem (discarding boundary terms since the boundary is at infinity) to shift the Laplacian in the second

÷”
ij k ‰Â k Ht-RêcL ÷ ”£ ∑ ÷” ∑ 1 y
jj‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “
ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Jt - ÅÅÅÅÅÅ N z` - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j ÅÅÅÅÅÅÅÅÅÅÅÅ “£2 ÅÅÅÅÅÅ + dHtL “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ zzzz
∑A m0 1 R m0 1
∑t 4p r c 4 p m0 e0 k 2p 4pR ∑ z£ r£ ∑z r {
k ‰Â k Ht-RêcL ÷ ”£ ∑ ÷” z
= - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ dHx” £ L - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ
m0 1 1 1
4p r 4 p e0 2p R ∑z £ 4 p e0 r3
÷ ”£
÷ ”£ ÷ ” ∑z
Again we integrate the second term by parts to move the “ ÅÅÅÅ∑ÅÅÅÅ£Å away from the d-function. We want to use the
latter to do the x£ integral, but first we rewrite “ ÅÅÅÅ∑ÅÅÅÅ£Å Ø I-“M I- ÅÅÅÅ∑ÅÅÅÅ M so we can pull it out of the x£ integral:
∑z ∑z
÷”
ij÷ ” ∑ ‰Â k Ht-RêcL yz ” £ ÷” z
ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ jj“ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz dHx L - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “
j z
∑A m0 1 1 k 1
k ∑z {
ÅÅÅÅÅÅÅÅ
∑t 4p r 4 p e0 2p 4 p e0 r3
k ÷ ” ∑ ‰Â k Ht-rêcL
R
÷” z
= - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ
m0 1 1 1
4p r 4 p e0 2 p ∑z r 4 p e0 r3
7

Ä É Ä ÉÑ
÷ ” ∑ ‰-Â k rêc ÷ ” ÅÅÅÅijj Â k ‰-Â k rêc ‰-Â k rêc yz i ∑ yÑÑÑÑ ÷ ” ÅÅ i Âk 1 y Ñ
“ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = “ ÅÅÅjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz j ÅÅÅÅÅÅÅÅÅ rzÑÑÑ = -“ ÅÅÅÅ‰-Â k rêc jj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz cos qÑÑÑÑ
j z
ÅÅÇk r2 { k ∑ z {ÑÑÖ ÅÇ k cr r2 { ÑÖ
ÄÅ Â k 2 yÑÑ É
∑z
Åi 1 yi Âk y i Âk ÷” i Âk 1 y ÷”
r cr

= - ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz jj- ÅÅÅÅÅÅÅÅÅ zz + jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅ zzÑÑÑÑ cos q ‰-Â k rêc “ r - ‰-Â k rêc jj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz “ cos q
ÅÇk c r r {k c { k cr r {Ö Ñ k cr r2 {
jij ÅÅÅÅ2ÅÅÅÅ +
k2 y
2 2 3

i Âk 1 y i sin q ` y
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz cos q ‰-Â k rêc r` - ‰-Â k rêc jj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ qzz
jj 3
2Âk
kr c r{ k cr r2 { k {
=

ÅÄÅ Â k É
Ñ
ÑÑ
cr 2 2 r
1 yÅi
= ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅÅ
+ ÅÅÅÅÅÅÅÅ zz I2 cos q r` + sin q qM - ÅÅÅÅÅÅÅÅÅÅÅÅÅ cos q r` ÑÑÑÑ ‰-Â k rêc
ÅÅÇk c r2 ÑÑÖ
` k2
r3 { c2 r
÷”
Now when we plug this back into the integral in ∑ A ë ∑t we can convert it all back to d-functions by using the
Fourier transform formula F HnL HwL = Ÿ-¶ ¶ k
ÅÅÅÅÅÅÅÅÅ H-Â kLn f HkL ‰Â w k with F Ø d, f Ø 1, w Ø t - R ê c for our case:
2p
÷”
1 ÄÅÅi 1 y
ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ d£ Ht - R ê cL + ÅÅÅÅÅÅÅÅ dHt - R ê cLzz I2 cos q r` + sin q qM
4 p e0 ÅÇk c r2
∑A m0 1
{
1 `

ÉÑ
∑t 4p r
÷” z
3

Ñ
r

+ ÅÅÅÅÅÅÅÅÅÅÅÅÅ d≥ Ht - R ê cL cos q r` ÑÑÑÑ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ

ÑÖ 4 p e
1 1

c ÄÅÅi 1
c2 r r3
y
= - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Hc t - RL Icos q r` - sin q qM + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅjj- ÅÅÅÅÅÅÅÅ d£ Hc t - RL + ÅÅÅÅÅÅÅÅ dHc t - RLzz I2 cos q r` + sin q qM
0

4 p e0 ÅÇk r2
m0 c3 1 `
{
1 `

ÑÉÑ
4p r r3
÷” z
+ ÅÅÅÅÅ d≥ Hc t - RL cos q r` ÑÑÑÑ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ
ÑÖ 4 p e0
1 1

c ÅÄÅi 1 y ` ÑÉÑ ÷” z
r3

= - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ÅÅÅÅjj ÅÅÅÅÅ d£ Hc t - RL - ÅÅÅÅÅÅÅÅ dHc t - RLzz I2 cos q r` + sin q qM - d≥ Hc t - RL sin q qÑÑÑÑ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ
r

4 p e0 r ÇÅk r ÑÖ 4 p e0
`
{
1 1 1
r2 r3

In the second step I've used an identity for d-functions d Ha xL = d HxL ê †a§ to rewrite d Ht - R ê cL = c d Ht - R ê cL, then
÷” ÷” ÷” ÷” ÷” ÷”
∑A
ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅ1ÅÅÅÅÅÅÅÅ d HtL “ ÅÅÅÅz3ÅÅ - ÅÅÅÅ
∑A
÷”
every derivative costs a factor of c. Now plug this into E = -“ F - ÅÅÅÅ ÅÅÅÅÅ , where the “ ÅÅÅÅz3ÅÅ
∑t 4 p e0 r ∑t r
∑A
cancels the one from ÅÅÅÅ
ÅÅÅÅÅ :

c ÄÅÅi d£ Hc t - RL É
∑t

÷” dHc t - RL y ` ÑÑ
E = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz I2 cos q r` + sin q qM - d≥ Hc t - RL sin q qÑÑÑÑ
4 p e0 r ÅÇk ÑÖ
`
{
1
r r2

The Cartesian components is straightforward plug-in of r` = cos f sin q x` + sin f sin q y` + cos q z` and
`
q = cos f cos q x` + sin f cos q y` - sin q z` . The result is a not-very-enlightening mess that will just be retyping the
stuff in Jackson, so instead I'll outline the procedure in words. Looking at the x component we see that the relevant
`
parts of r` and q all get multiplied by cos f and the correct factor of either sin q or cos q to enable us to pull the
angular terms out. The first and second term then adds to give the factors of 3 that appear in the formula, and the
signs are exactly as they should be. The y component works the same way. For the z component each of the
cosines and sines gets squared and the sines flip sign. The last term immediately produces what we want. The
second term can be converted to cosines using sin2 q + cos2 q = 1, which gives the factor of 3 cos2 q - 1.
÷”
Anyway, we see from the d-functions above that E is manifestly causal (t doesn't appear anywhere else).